Altitude training for sea level performance - Levine, B. D. (1998)
Altitude training is frequently used by elite athletes to enhance sea level performance. However with traditional altitude training: living and training at altitudes > 2,000m, many athletes do not thrive and controlled studies have failed to show an overall improvement. Recently, the "living high-training low" model has been introduced in which athletes live at altitudes > 2,500m but travel below 1,500m to train. This model takes advantage of the acclimatization response to improve oxygen transport, but eliminates the detraining associated with training at altitude. In general, even elite endurance athletes can expect a 3-5% increase in VO2max, and a 1-2% improvement in racing time after 4 weeks of such a training camp, though significant individual variability remains. The source of this variability appears to be twofold: 1) living high enough to get a sufficient increase in erythropoietin and a consequent increase in red cell mass, and; 2) training low enough to allow adequate running speed and oxygen flux during high intensity interval training. A number of ingenious adaptations of this model have become popular, including diluting a dormitory room with sufficient nitrogen to induce ambient hypoxia (so-called "nitrogen houses") or sleeping in a hypobaric chamber, but the optimal "dose" of altitude in terms of how high, how many hours/day, how long, etc. remains to be determined. The ethics of such approaches, in comparison to clearly banned practices such as blood doping, or the use of exogenous recombinant erythropoietin have recently been debated. For all models, iron stores must be normal before attempting an altitude training camp and iron deficient athletes (based on determinations of serum ferritin concentrations) will not improve.